Magnesium-ligand cooperation enables regioselective transfer hydrogenation of quinolines to 1,2-dihydroquinolines - Mahata, Biplab; Sharma, Jyoti; Vanka, Kumar; Sen, Sakya S. (Organic Letters, 2026)
We report the first magnesium-catalyzed regioselective reduction of quinolines to 1,2-dihydroquinolines, utilizing H3N & centerdot;BH3. This protocol operates under mild conditions and tolerates a broad range of functional groups. Comprehensive mechanistic investigations, including kinetic analysis, deuterium labeling, and density functional theory calculations, elucidate a concerted hydride transfer pathway. This work serves as a blueprint for employing s-block metals with high-precision reactivity, which are traditionally reserved for transition metals.